Targeted CRM197-PEG-PEI/siRNA Complexes for Therapeutic RNAi in Glioblastoma - Achim Aigner; Chantal C.M. Appeldoorn; Sabrina Höbel; Pieter J. Gaillard (MDPI AG, 2011)
RNA interference (RNAi) allows the specific knockdown of tumor relevant genes. To induce RNAi, the delivery of small interfering RNAs (siRNAs) is of crucial importance. This is particularly challenging for their therapeutic applications in vivo. Low molecular weight branched polyethylenimine (PEI) is safe and efficient for nucleic acid delivery including small RNA molecules, based on its ability to electrostatically complex siRNA molecules, thereby protecting them from nuclease degradation. The nanoscale PEI/siRNA complexes are endocytosed by cells prior to intracellular complex release from the lysosome and cytoplasmic release of the siRNAs from the complexes. Chemical modification and ligand decoration of the complexes aim at introducing target tissue specificity and further increased efficacy of PEI-mediated siRNA delivery. CRM197 is a mutated, non-toxic diphtheria toxin (DT) that binds to the membrane-bound precursor of HB-EGF-like growth factor/diphtheria toxin receptor highly expressed in glioblastoma cells. Likewise, the growth factor pleiotrophin (PTN/HB-GAM/HARP) is overexpressed in glioblastoma and is rate limiting for tumor growth, thus representing an attractive target gene for therapeutic knockdown approaches. PEGylation of PEI was performed to reduce the surface charge, and by CRM197 coupling we prepared a modified PEI for siRNA delivery into glioblastoma cells. The novel PEI conjugates were analyzed for their complexation efficiency and optimal mixing ratios, and complexes were physicochemically characterized regarding stability, size and zeta potential. The biological activity of the complexes was confirmed in cell culture by reporter gene knockdown. For the therapeutic treatment of subcutaneous human gliobastoma xenografts in athymic nude mice, we systemically injected the modified PEI/siRNA complexes targeting PTN. Antitumor effects based on PTN knockdown demonstrated the advantage of tumor-targeted CRM197-PEG-PEI/siRNA over untargeted PEG-PEI polyplexes. Thus, we establish targeted CRM197-PEG-PEI-based complexes for siRNA delivery in vivo, and show therapeutic effects of CRM197-PEG-PEI/siRNA-mediated knockdown of PTN.